First summary of Cossidae of Sierra Leone (West Africa) (Lepidoptera: Cossidae) - R. V. Yakovlev; Gy. M. Laszlo (SHILAP, 2019)
Present paper contains the list of Cossidae (Lepidoptera) collected in Sierra Leone. Sixteen species have been recorded, seven of them are found in the fauna of Sierra Leone for the first time: Macrocossus toluminus (Druce, 1887), Mirocossus politzari Yakovlev, 2011, Assegaj clenchi Yakovlev, 2006, Aethalopteryx grandiplaga (Gaede, 1930), Tarsozeuzera livingstoni Yakovlev, 2006, Strigocossus elephas Yakovlev, 2013, and Holcoceroides ferrugineotincta Strand, [1913].